1972
DOI: 10.1007/bf00167507
|View full text |Cite
|
Sign up to set email alerts
|

The application of cost-benefit analysis to transport investment projects in Britain

Abstract: This paper explains the need for the application of cost-benefit analysis to the evaluation of alternative projects for investment in the transport field and outlines briefly the historical development of the technique. The results of a comparative survey of a number of cost-benefit studies which have been carried out in Britain and some conclusions as to their thoroughness and comprehensiveness (or otherwise) are presented.The article concludes with a number of specific and detailed recommendations to remedy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Historically, benefit-cost analysis has been used to evaluate alternative transportation projects and to aid in decision-making and policy formulations with equity considerations, discounted cash flow techniques, and sensitivity analysis for benefit-cost studies of the future (Barrell and Hills, 1972). It has been recommended for comparing transportation projects cost analysis over traditional benefit-cost analysis which aggregates all monetizable cost components, including "cost savings" (these were referred to as "benefits" in traditional analysis techniques) (DeCorla-Souza et al, 1997).…”
Section: Benefit-cost Analysis For Transportation Projects: a Literat...mentioning
confidence: 99%
“…Historically, benefit-cost analysis has been used to evaluate alternative transportation projects and to aid in decision-making and policy formulations with equity considerations, discounted cash flow techniques, and sensitivity analysis for benefit-cost studies of the future (Barrell and Hills, 1972). It has been recommended for comparing transportation projects cost analysis over traditional benefit-cost analysis which aggregates all monetizable cost components, including "cost savings" (these were referred to as "benefits" in traditional analysis techniques) (DeCorla-Souza et al, 1997).…”
Section: Benefit-cost Analysis For Transportation Projects: a Literat...mentioning
confidence: 99%
“…Gallatin was U.S. Secretary of the Treasury at that time and he recommended comparisons in terms of costs and benefits in water infrastructure projects. Perhaps the first widespread use of CBA was instituted by the 'Federal Navigation Act-1936' of the U.S.A., which mandated the usage of cost-benefit analysis to assess proposed waterway infrastructure [18]. In 1939, the use of CBA was significantly expanded when the 'Flood Control Act' required CBA analysis for all new projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In practice, however, it is impossible to avoid making some such assumption whenever it is desired to offset benefits accruing to one group against costs borne by another. In a study of 19 cost-benefit analyses carried out in Britain in the period 1960/71, Barrell and Hills (1972) point out that all, in effect, have assumed that the marginal utility of money is equal for all members of society. Consistent with this they found that few studies made any substantial attempts to identify separately the "social incidence" of the various costs and benefits.…”
Section: Comparison Of the Two Measuresmentioning
confidence: 99%